Analysis of Online Gender-Based Violence (OGBV) in Singgahan Subdistrict: A Perspective of Positive Law in Indonesia - Gita Arum Buana; Syamsul Arifin; Siti Zakiyatun Nisa; Wiranto Wiranto (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
The law functions to regulate daily life and address crimes and deviations across various aspects of society. Crimes continue to occur in many countries, including Indonesia, and may happen either directly or through online platforms. In such cases, women are often the primary victims of violence, with one example being Online Gender-Based Violence (OGBV). OGBV may take the form of intimidation, sexual harassment, exploitation, and more. However, this issue is protected under existing laws, including the ITE Law. This study aims to investigate OGBV cases in Singgahan District. It employs qualitative research methods, including observation, interviews, and documentation, to describe and analyze the problem. The findings indicate that OGBV frequently occurs in Singgahan District due to factors such as social norms, access to increasingly advanced technology, lack of education about mental and emotional health, anonymity, inadequate law enforcement, stigma, and environmental influences. Efforts to address this issue include education, mentoring, law enforcement training, policymaking, collaboration with civil society, and family support. It is essential to remain vigilant and proactive in protecting ourselves wherever we are and to report any harmful incidents without hesitation